Answer:
The coefficient of the squared term of the equation is 1/9.
Step-by-step explanation:
We are given that the vertex of the parabola is at (-2, -3). We also know that when the <em>y-</em>value is -2, the <em>x-</em>value is -5. Using this information we want to find the cofficient of the squared term in the parabola's equation.
Since we are given the vertex, we can use the vertex form:
![\displaystyle y=a(x-h)^2+k](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Da%28x-h%29%5E2%2Bk)
Where <em>a</em> is the leading coefficient and (<em>h, k</em>) is the vertex.
Since the vertex is (-2, -3), <em>h</em> = -2 and <em>k</em> = -3:
![\displaystyle y=a(x-(-2))^2+(-3)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3Da%28x-%28-2%29%29%5E2%2B%28-3%29)
Simplify:
![y=a(x+2)^2-3](https://tex.z-dn.net/?f=y%3Da%28x%2B2%29%5E2-3)
We are also given that <em>y</em> = -2 when <em>x</em> = -5. Substitute:
![(-2)=a(-5+2)^2-3](https://tex.z-dn.net/?f=%28-2%29%3Da%28-5%2B2%29%5E2-3)
Solve for <em>a</em>. Simplify:
![\displaystyle \begin{aligned} -2&=a(-3)^2-3\\ 1&=9a \\a&=\frac{1}{9}\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%20-2%26%3Da%28-3%29%5E2-3%5C%5C%201%26%3D9a%20%5C%5Ca%26%3D%5Cfrac%7B1%7D%7B9%7D%5Cend%7Baligned%7D)
Therefore, our full vertex equation is:
![\displaystyle y=\frac{1}{9}(x+2)^2-3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B1%7D%7B9%7D%28x%2B2%29%5E2-3)
We can expand:
![\displaystyle y=\frac{1}{9}(x^2+4x+4)-3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B1%7D%7B9%7D%28x%5E2%2B4x%2B4%29-3)
Simplify:
![\displaystyle y=\frac{1}{9}x^2+\frac{4}{9}x-\frac{23}{9}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B1%7D%7B9%7Dx%5E2%2B%5Cfrac%7B4%7D%7B9%7Dx-%5Cfrac%7B23%7D%7B9%7D)
The coefficient of the squared term of the equation is 1/9.